Efektifitas Model Pembelajaran Inkuiri untuk Mengukur Kemampuan Berpikir Logis Siswa Kelas IV pada Pembelajaran IPS di SD Negeri 08 Pedamaran - Nathasyah, Anisa; Idris, Muhamad; Suryani, Ida (Indonesian Research Journal on Education, 2023)
The purpose of this study was to determine the effectiveness of the inquiry learning model to measure students' logical thinking skills in social studies class IV at SD Negeri 08 Pedamaran. This research is an experimental research form of pseudo experiment (Quasi Experiment), the research design used is a "Pretest-Posttest Control Group design with randomized group selection". The study population was allfourth-grade students of SD Negeri 08 Pedamaran. The research sample is class IVB (Experiment) and class IVA (Control) with a total of 64 students Class IVA has As many as 32 and class IVB has 32 students. data collection is done by using a learning outcome test in the form of a Pretest and Posttest. In the "Equal variances assumed" section it is known that the sig value (2-tailed) is 0.000 <0.05 or it can also be seen from the t_hitung = 4.521> t_ (table) = 1.166980, it is concluded that there is a significant difference between the average learning outcomes in the experimental class and the control class. Andalso seen from the value of the "Meaningful difference" is 18.12500. this value shows the difference between the average student learning outcomes in the experimental class and the control class 74.0625 - 55.9375 = 18.12500 and the difference is 10.11106 to 26.13894.